Economics and the Public Purpose - Galbraith Kenneth John (Penguin Books, 1973)
The concept of the private affluence amid public squalor firat introduced in the Affluent Society has ''conditioned the thinking of half a generation'', to quote Michael Stewart in the Times. Preface, The Forest, The Uses of an Economic System and of Economics, The Neo-Classical Model, The General Theory of Advanced Development, The Market System, Self Exploitation and Exploitation, The Planning System, The Affirmative Purposes, Persuasion and Power, The Transnational System, The Two Systems, The Economics of Anxiety: A Test, A General Theory of Reform, The Emancipation of Belief, Policy for the Market, The Socialist Imperative, The Public State, Index.